Hedging in Academic Writing - A Pedagogically-Motivated Qualitative Study - Chek Kim Loi; Jason Miin-Hwa Lim (2015)
The present study explores the use of hedges in academic writing based on Hyland's (1996) pragmatic framework of hedging orientations. It also elicits insight from specialist informants on the use of hedges in academic writing. The corpus comprises thirty randomly-selected research article discussions (published between 2010-2014) from the Journal of English for Academic Purposes. The analysis reveals that a repertoire of lexical signals and hedging strategies have been used to realize the different hedging orientations employed in the corpus. Informants stated that second language learners’ inability to use hedges in their academic prose could be due to socio-cultural factor, classroom instruction, disciplinary culture and disciplinary appeals. The present study has pedagogical implications.